3D 프린팅 기술을 이용한 원료에 대한 방사선 차폐능 평가: FDM 방식의 3D 프린팅 기술을 중심으로 - 이홍연; Hongyeon Lee; 김동현; Donghyun Kim (한국방사선학회 논문지, 2018)
3D 프린팅 기술은 4차산업 혁명 중 제조업의 혁신적인 기술로서 전망되고 있으며, 현재 바이오 · 의료분야를 포함한 다양한 분야에서 활용되고 있다. 본 연구에서는 이러한 3D 프린팅 기술을 이용한 제작 원료에 대한 방사선 차폐능을 평가하고자 몬테카를로 전산모사를 통해 프린팅 원료에 대한 검증을 수행하였다. 현재 범용으로 사용되는 FDM 방식의 3D 프린터에서 이용 가능한 원료들을 대상으로 하였으며, ICRU phantom과 차폐체를 모의 모사한 후 방사선의 종류 및 에너지에 따른 입자 플루언스 평가를 통해 차폐 효과에 대해 분석하였다. 그 결과, 광자선의 경우 에너지 증가에 따라 차폐 효과는 점차 감소되는 경향을 보였고, 원료별 차폐 효과는 TPU, PLA, PVA, Nylon, ABS 순서로 점차적으로 낮아지는 결과를 나타냈다. 중성자선의 경우, 5~10 mm의 낮은 두께에서 반대로 선속이 증가되는 현상을 보였으나, 일정 두께 이상에서는 유효한 차폐 효과를 나타내었으며, 프린팅 원료별 차폐 효과는 Nylon, PVA, ABS, PLA, TPU 순서로 점차 낮아지는 결과를 보였다. 3D printing technology is expected to be an innovative technology of the manufacturing industry during the 4th industrial revolution, and it is being used in various fields including biotechnology and medical field. In this study, we verified the printing materials through Monte Carlo simulation to evaluate the radiation shielding ability of the raw material using this 3D printing technology. In this paper, the printing materials were selected from the raw materials available in a general-purpose FDM-based 3D printer. Simulation of the ICRU phantom and the shielding system was carried out to evaluate the shielding effect by evaluating the particle fluence according to the type and energy of radiation. As a result, the shielding effect tended to decrease gradually with increasing energy in the case of photon beam, and the shielding effect of TPU, PLA, PVA, Nylon and ABS gradually decreased in order of materials. In the case of the neutron beam, the neutron intensity increases at a low thickness of 5 ~ 10 mm. However, the effective shielding effect is shown above a certain thickness. The shielding effect of printing material is gradually increased in the order of Nylon, PVA, ABS, PLA and TPU Respectively.